2016
DOI: 10.1016/j.nedt.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence experienced by nursing students: A UK survey

Abstract: Aims: To appreciate the nature and scope of workplace violence amongst a sample of the UK nursing student population during clinical placement and to recommend strategies universities can implement to successfully manage the impact.Background: Workplace violence is defined as a violent act(s) directed toward workers and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
162
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(179 citation statements)
references
References 26 publications
9
162
1
7
Order By: Relevance
“…A study from Egypt found that 38% of nursing students experienced a moderate degree of bullying (Kassem, Elsayed, & Elsayed, 2015). A similar incidence (42%) was recently reported by UK nursing students (Tee et al, 2016).…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…A study from Egypt found that 38% of nursing students experienced a moderate degree of bullying (Kassem, Elsayed, & Elsayed, 2015). A similar incidence (42%) was recently reported by UK nursing students (Tee et al, 2016).…”
Section: Introductionsupporting
confidence: 87%
“…Recent work identifies nurses and clinical facilitators as the main perpetrators of bullying (Clarke, Kane, Rajacich, & Lafreniere, 2012;Tee et al, 2016), reflecting the comments of participants in this study. A perception of bullying as a being 'part of the job' contributes significantly to the problem.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Moreover tolerance values are above 0.2. 74 In order to predict perceived workplace security from predictors, forced entry method regression was performed on the total data of 417 respondents. Two blocks were formed of identified predictors under the criteria of evidences in literature.…”
Section: Discussionmentioning
confidence: 99%